Effect of taurine on some antioxidant levels in rats exposed to oxidative stress by hydrogen peroxide - Sameera Al-Kateb; Ahmed Thanoon (College of Education for Pure Sciences, 2008)
Abstract This study included the use of hydrogen peroxide 0.5% in drinking water to induce an oxidative stress in male rats and asses the ability of the different concentrations of taurine for protection or prevention from the oxidative stress.The following parameters in serum during 10, 20 and 30 days were measured in the serum: vit. C, vit. E, glutathione, malondialdehyde, SOD activity, peroxynitrite, albumin, selenium, zinc and copper Fourty male rats (with age of 3-4 months and weight of 300-400 gm) were divided into 4 groups depending on the body weigh: group [1] as a control group received drinking tap water, group [2] : treated with H2O2 0.5% in drinking water, group[3] : treated with H2O2 and taurine 0.5%, group[4] : treated with H2O2 and taurine 1% . Hydrogen peroxide treatment revealed a significant reduction in the vit C, vit E, GSH, albumin, Se, Zn and Cu levels, and a significant increase in the MDA, peroxynitrite and SOD activity levels in the serum for the most of the treatment periods compared with control group (P<0.05). The different concentrations of taurine tretment revealed a signifigant effects in the protection from the oxidative stress induced by H2O2. The effects of taurine ratio 0.5% were significant on the serum levels of vit C, SOD, peroxynitrite, Se and on the MDA level in the serum. The taurine 1% ratio produced maximum effects on vit E, GSH, albumin, Zn and Cu levels in the serum.